Zonation of Nipah Beach Ecosystem in North Lombok District to Support Sea Turtle Conservation Efforts - Maiser Syaputra; Endah Wahyuningsih; Kornelia Webliana; Irwan Mahakam Lesmono Aji; Pande Komang Suparyana; Andi Tri Lestari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nipah Beach is facing challenges of development, economic growth, and high community demand for land, which may negatively impact the sustainability of sea turtles. To mitigate this issue, the ecosystem of Nipah Beach must be appropriately zoned. The goal of beach ecosystem zonation is to allocate areas around the coast to the community and stakeholders based on the sensitivity of sea turtle habitats. This research aims to 1. Analyze the suitability of Nipah Beach in North Lombok Regency as a sea turtle habitat. 2. Design the zonation of the sea turtle conservation area in Nipah Beach, North Lombok Regency. The study uses an observation method, namely collecting data through direct inspection or careful inspection in the field or research location by dividing Nipah Beach into several observation stations. The results are analyzed using scoring techniques and spatial modeling, resulting in a map. Research results show that the suitability level of Nipah Beach as a sea turtle habitat ranges from 15-46 points, with station two having the highest score and station six having the lowest. Stations two and three, and part of station five are prioritized as protection zone areas, station four and part of station five and one as a captive zone area, and the rest as limited-use zones